EFFECT OF POLLINATION METHODS AND POLLEN DILUTION ON SOME CHEMICAL CONSTITUENTS OF FARD DATES AT DIFFERENT STAGES OF FRUIT DEVELOPMENT - El-Mardi, M.O.; Labiad, S.N.; Consolacion, E.; Addelbasit, K.M. (Emirates Journal of Food and Agriculture, 1995)
Please see the scanned pdf version in full text